(untitled) (Proceedings of Southern Federal University. Philology, 2021)
Larisa D. Bednarskaya (Orel, Russian Federation) The article continues the series of publications on the problems of multilevel comprehension of systematics in modern educational processes. This determines the attitude to the Russian language course as a discipline of the meta-subject integrative level, which allows to integrate the acquired competencies with other subjects of the school cycle. On the basis of the assimilation of theoretical material tendency to diagnose the formation of competencies in the functional aspect is more clearly defined, when the basis of the norms of language focuses on language: a functional-communicative aspect backbone relies on a linguistic basis. Test materials for the exam on the Russian language correspond to the functional-communicative filling the content of the Programs of the GEF. Awareness of the systematic nature of the processes of studying the subject and diagnosing its assimilation allows to intensify both its assimilation and the diagnosis of the formed competencies, opens up prospects for optimizing the educational process. The article offers examples of compression of theoretical material of different volumes, which help to generalize a huge layer of speech implementations and easily learn them. Key words: system-activity paradigm of modern education, consistency of the control and measurement materials of the Unified State Exam, the prospects for optimizing the diagnosis of acquired competencies. DOI 10.18522/1995-0640-2021-2-214-227